2018
DOI: 10.1101/413054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Onecut factors and Pou2f2 regulate the distribution of V2 interneurons in the mouse developing spinal cord

Abstract: 32 Acquisition of proper neuronal identity and position is critical for the formation of neural 33 circuits. In the embryonic spinal cord, cardinal populations of interneurons diversify into 34 specialized subsets and migrate to defined locations within the spinal parenchyma. 35 However, the factors that control interneuron diversification and migration remain poorly 36 characterized. Here, we show that the Onecut transcription factors are necessary for proper 37 diversification and distribution of the V2 inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…V2a interneurons have recently been shown to consist of two major subgroups that have different settling positions: a medial subgroup expressing Nfib and Neurod2 and a lateral subgroup that expresses Shox2 and Zfhx3 (Hayashi et al, 2018). Furthermore, the lateral subgroup seems to further diversify into subgroups labelled by Shox2 and Maf/Onecut TFs (Francius et al, 2013;Harris et al, 2018). Consistent with this, hierarchical clustering of the single cell transcriptome data revealed four major subtypes of V2a neurons ( Fig 4D).…”
Section: Clustering Of Neurons Predicts Novel Neuronal Subtypes and Tsupporting
confidence: 70%
“…V2a interneurons have recently been shown to consist of two major subgroups that have different settling positions: a medial subgroup expressing Nfib and Neurod2 and a lateral subgroup that expresses Shox2 and Zfhx3 (Hayashi et al, 2018). Furthermore, the lateral subgroup seems to further diversify into subgroups labelled by Shox2 and Maf/Onecut TFs (Francius et al, 2013;Harris et al, 2018). Consistent with this, hierarchical clustering of the single cell transcriptome data revealed four major subtypes of V2a neurons ( Fig 4D).…”
Section: Clustering Of Neurons Predicts Novel Neuronal Subtypes and Tsupporting
confidence: 70%
“…V2a interneurons have recently been shown to consist of two major subgroups that have different settling positions: a medial subgroup that expresses Nfib and Neurod2, and a lateral subgroup that expresses Shox2 and Zfhx3 (Hayashi et al, 2018). Furthermore, the lateral subgroup appears to diversify further into subgroups that are labelled by Shox2 and Maf/onecut family TFs (Francius et al, 2013; Harris et al, 2018 preprint). Consistent with this, hierarchical clustering of the single cell transcriptome data revealed four major subtypes of V2a neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Onecut TFs, for example, are required in early-born V1 and MNs for the specification of Renshaw cells and medial lateral motor column (LMCm) neurons respectively (Roy et al, 2012; Stam et al, 2012). Furthermore, Onecut TFs and Pou2f2 control the distribution of neurons from multiple dorsal-ventral domains (Harris et al, 2019; Kabayiza et al, 2017; Masgutova et al, 2019). Neurod2/6 control neuropeptide expression in inhibitory neurons in the dorsal horns of the spinal cord (Bröhl et al, 2008) and characterization of V2a neuron heterogeneity revealed that Zfhx3 and Neurod2/Nfib divide this neuronal class into a lateral and medial population (Hayashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%